INVENTARISASI SERANGGA-SERANGGA PADA PERTANAMAN NENAS (Ananas comosus (L.) Merr.) MONOKULTUR DAN POLIKULTUR DI KABUPATEN BOLAANG MONGONDOW - Mariane K. Lumananw; Juliet E.M. Mamahit; Moulwy F. Dien; Guntur M.J. Manengkey (COCOS, 2013)
ABSTRACT Pineapples are a fruit that grows on bushes with the scientific name Ananas comosus. They are native to Brazil (South America) and have been domesticated there since before Columbus’ advent. In the 16th century, Spaniards brought pineapples to the Philippines and the Malaysian Peninsula, then into Indonesia in the 17th century. This study aims to know the insects associated to monocultured and polycultured pineapples (A. comosus) and to know the dominant insects among said plants. This study is expected to inform about significant insects, both as pests as well as natural enemies, so it can be managed in pineapple planting systems and used in pineapple pest control. This study was done in the pineapple plantation village of Lobong and Mongkunai, regency of BolaangMongondow. Laboratory observations were done in the Weeds and Entomology laboratory of the Agriculture Faculty, University of Sam Ratulangi. Observation of insects on plant pineapples were calculated using the trap sinks. Insect observations showed that there are 6 insect orders founded to monocultured and polycultured pineapple plants, namely: Coleoptera Orders, Orthoptera Orders, Diptera Orders, Hymenoptera Orders, Collembola Orders and Lepidoptera Orders. Dominant insects in the monocultured and polycultured pineapple plantations are firstly from the Hymenoptera Order (Family of Formicidae), next from the Orthoptera Order (Family of Acrididae), third from the Coleoptera Order (Family of Scolytidae) and fourth from the Diptera Order (Familiy of Drosophilidae). Key words : Pineapple Plant (Ananas comosus), Inventory of insects, Monocultured And Polycultured.